2019
DOI: 10.2147/cmar.s194637
|View full text |Cite
|
Sign up to set email alerts
|

<p>The predictive value of high-density lipoprotein for ocular metastases in colorectal cancer patients</p>

Abstract: Purpose: Colorectal cancer (CRC) is a common tumor of the digestive tract that tends to metastasize and leads to high mortality. Ocular metastases (OM) from colorectal cancer are being increasingly diagnosed, and they can lead to a poor prognosis. Serum lipids are a known risk factor for cardiovascular disease, and are also relevant to the occurrence of CRC. In this study, we examined the levels of serum lipids and tried to determine whether there were correlations with the occurrence of OM in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…As mentioned above, those may provide potential mechanisms for the differences of serum lipid levels in male NPC patients with or without eye metastasis, for example, through exosomes or miRNA [51]. The inner mechanisms are thought-provoking, and our team have been studying the risk factors of eye metastasis of many different cancers, we once found high-density lipoprotein can be a sensitive index for eye metastases in colorectal cancer patients [52]. Our study aims to find sensitive serological markers as an auxiliary reference standard for early diagnosis of eye metastasis of nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 83%
“…As mentioned above, those may provide potential mechanisms for the differences of serum lipid levels in male NPC patients with or without eye metastasis, for example, through exosomes or miRNA [51]. The inner mechanisms are thought-provoking, and our team have been studying the risk factors of eye metastasis of many different cancers, we once found high-density lipoprotein can be a sensitive index for eye metastases in colorectal cancer patients [52]. Our study aims to find sensitive serological markers as an auxiliary reference standard for early diagnosis of eye metastasis of nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 83%
“…Risk factors obtained by the statistical analysis were useful to predict distant metastases in clinical practice. Studies of risk factors for various metastases are summarized in Table 5 5,6,9‐12 …”
Section: Discussionmentioning
confidence: 99%
“…Studies of risk factors for various metastases are summarized in Table 5. 5,6,[9][10][11][12] In the present retrospective study, we explored the risk factors for OM in 1192 patients with IDC and analyzed their diagnostic values. As patients in the OM group were more likely to have other metastases and their diseases were also in advanced stages, they often had poor prognosis.…”
Section: Roc Curve Analysis For Combined Risk Factorsmentioning
confidence: 99%
“…In a study by Healy et al [ 21 ], the serum HDL-C level was significantly associated with a more advanced pathological stage of CRC and lymph node involvement. Other studies have found no difference in HDL-C levels among CRC patients with and without distant metastases [ 22 ], or even increased HDL-C levels in those with ocular metastases [ 23 ].…”
Section: Hdl-c Levels and Hdl Subclass Distribution In Crcmentioning
confidence: 99%